(untitled) (Research, Society and Development, 2020)
It was proposed to verify the effect of the total substitution of soy by canola and crambe grains in the diet of crossbred lambs, in order to evaluate the chemical, instrumental and sensory characteristics of the meat of the animals fed under these grains. Twenty-three samples of the Longissimus lumborum muscle were used, from SRD lambs (mixed breed), non-castrated males, with an average age of 70 days, average initial body weight of 20.0 ± 4.0 kg. Of the 23 animals used, seven were destined for soybean diet, eight with canola grain and eight with crambe grain. The design was completely randomized with the factor evaluated as the total replacement (100%) of the ground soybeans considered control (GSO) by ground canola beans (GCA) and ground crambe beans (GCR). The sensory analysis data were submitted to Principal Component Analysis and the centesimal and instrumental analyzes were tested in orthogonal contrasts in relation to the different grains. The ration provided was in the form of a complete diet, with 75% concentrate and 25% roughage (Brachiaria brizantha cv Piatã hay). The results showed a higher moisture content in the meat of animals fed with canola, as well as in the instrumental characteristics (loss of cooking and intensity of red). For the other characteristics, there was no effect. The sensory analysis showed that the tasters preferred the meat of animals fed with soy and canola grains, pointing to the market potential. Canola and crambe grains can replace soy in the diet of lambs finished in feedlot, without affecting the centesimal, instrumental and mainly sensory characteristics of the meat, contributing as a new grain alternative in animal production.